Analysis of service quality and income of BPJS health participants during the Covid-19 pandemic: A case study - Erizal, Erizal (International Journal for Educational and Vocational Studies, 2022)
This study is to find out the quality of BPJS health services to the community during the covid-19 pandemic in the Pondok Benda village is quite satisfied and the income of the people is decreasing due to the covid-19 pandemic, and to find out the ability to pay BPJS health contributions in the Pondok Benda village is quite high. The Social Security Administering Body (BPJS) for health is a very complex health service institution. BPJS Kesehatan cooperates with professional and capital-intensive hospitals.In this study, the author uses a survey research method with a discussion of research results using descriptive analysis. Descriptive analytical research, namely research that is intended to investigate circumstances, conditions, situations, events, activities and others, the results of which are presented in the form of a research report.the quality of service (procedures, requirements, clarity of officers, discipline of officers, responsibility of officers, ability of officers, speed of service, fairness, courtesy and friendliness of officers, environmental comfort and certainty of service costs) regarding BPJS health in Pondok Benda Pamulang Village, South Tangerang is sufficient good.Community income with indicators (high income, medium income and low/small income) on BPJS health inPondok Benda Pamulang, South Tangerang is quite good.